Peran Serikat Pekerja dalam Dunia Hubungan Industrial - Dhisa Tania Priyadi (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The relationship between company, workers and the government is related to the production of goods and services, then this relationship is known as Industrial Relations. An ideal industrial relationship is a relationship between company and workers that reflects the interests of both parties on a legal and humanitarian basis. Stories about workers in Indonesia are more about oppression, suffering, and the inability to defend themselves. The weak position of workers in front of the company makes workers feel the need for unity. The desire to unite which in the end gave birth to the Trade Unions. This study aims to analyze the role of trade unions in the formulation of industrial relations policies. This study uses a qualitative research approach. This study uses secondary data through literature study techniques. Trade unions have the function of representing workers in resolving disputes, negotiating Collective Labor Agreements to create harmonious and equitable industrial relations. The trade unions accommodate every aspiration expressed by workers. Trade unions as actors representing workers carry out their first role, namely participating in competing, providing suggestions in the process of formulating policies, equitable and pro-workers policies in the formulation of labor policies and public policies.